Proton pump inhibitors and sensitization of cancer cells to radiation therapy - Hebert, Kassidy A.; Bonnen, Mark D.; Ghebre, Yohannes T. (Frontiers in Oncology, 2022)
This review article outlines six molecular pathways that confer resistance of cancer cells to ionizing radiation, and describes how proton pump inhibitors (PPIs) may be used to overcome radioresistance induced by alteration of one or more of these signaling pathways. The inflammatory, adaptive, hypoxia, DNA damage repair, cell adhesion, and developmental pathways have all been linked to the resistance of cancer cells to ionizing radiation. Here we describe the molecular link between alteration of these pathways in cancer cells and development of resistance to ionizing radiation, and discuss emerging data on the use of PPIs to favorably modify one or more components of these pathways to sensitize cancer cells to ionizing radiation. Understanding the relationship between altered signaling pathways, radioresistance, and biological activity of PPIs may serve as a basis to repurpose PPIs to restore key biological processes that are involved in cancer progression and to sensitize cancer cells to radiation therapy.